Heterogeneity in the economic returns to schooling among Chinese rural–urban migrants, 2002–071. Issue 1 (19th November 2014) - Zhu, Rong
Abstract This paper analyses the returns to schooling among Chinese rural migrants using data from the 2002 and 2007 China Household Income Project. Our non‐parametric estimates show substantial heterogeneity in the schooling rates of return among migrant workers. While the returns to schooling for the overall sample have increased over time, this result is driven by the substantial increases in the schooling coefficients of female migrants. We expect the endogeneity biases in the estimated schooling returns to be decreasing after considering the change in the ability distribution of migrant workers during 2002–07.